2018
DOI: 10.1111/agec.12412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating irrigation investments in Malawi: economy‐wide impacts under uncertainty and labor constraints

Abstract: Irrigation expansion is critical to increase crop yields and mitigate effects from climate change in Sub-Saharan Africa, but the low profitability has led to little irrigation investments in the region so far. Using an integrated modeling framework, we simultaneously evaluate the returns to irrigation arising from both economic and biophysical impact channels to understand what determines the profitability of irrigation in Malawi. Our results confirm that the returns to irrigation cannot cover the costs in Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…through its impact on seedbed preparation, germination, root growth, absorption efficiency of fertilizers and crop growth) and farm economic performance (e.g. crop yields and farm income) (Huang et al, 2006;Kajisa and Payongayong, 2011;Li et al, 2020;Schuenemann et al, 2018;Silveira et al, 2020;Van Den Berg and Ruben, 2006;Wang et al, 2019). Therefore, enhancing the construction of irrigation infrastructure is considered a way to significantly improve the livelihoods of rural households.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…through its impact on seedbed preparation, germination, root growth, absorption efficiency of fertilizers and crop growth) and farm economic performance (e.g. crop yields and farm income) (Huang et al, 2006;Kajisa and Payongayong, 2011;Li et al, 2020;Schuenemann et al, 2018;Silveira et al, 2020;Van Den Berg and Ruben, 2006;Wang et al, 2019). Therefore, enhancing the construction of irrigation infrastructure is considered a way to significantly improve the livelihoods of rural households.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have shown that irrigation development improves farm economic performance and household welfare (e.g. Burney and Naylor, 2012;Dillon, 2011a, b;Foudi and Erdlenbruch, 2012;Huang et al, 2006;Kajisa and Payongayong, 2011;Koundouri et al, 2006;Li et al, 2020;Schuenemann et al, 2018;Silveira et al, 2020;Van Den Berg and Ruben, 2006;Weligamage et al, 2014). For example, Dillon (2011a) showed that improved irrigation access significantly increases household consumption and asset generation in Mali, while Foudi and Erdlenbruch (2012) revealed that irrigation usage tends to enhance farm economic performance by increasing maize yields and crop quality in France.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with the adoption of other technologies, low adoption of irrigation is linked to myriad constraints, resulting in limited availability, poor operation, and low profitability of irrigation schemes in Africa (Schuenemann et al 2018;You et al 2011). On the supply side, irrigation development in Africa has been constrained by poor governance structures, limited participation by private operators, negative health and environment consequences, and high cost of irrigation financing.…”
Section: Mechanizationmentioning
confidence: 99%
“…Agriculture in Egypt is dependent on irrigation and relies on the Nile River.8 Salinization levels are critical: 35% of Egypt's agricultural land suffers from high salinity, especially in the (over-populated) Nile Delta, where 60% of cultivated land in the northern Delta is salt affected (ICARDA, 2011).9 Irrigation waters of various quality levels have 123 distinct characterises with different impacts on crop yields, and biased cropping patterns 124 7 The literature of water related CGE is vast, see Liu et al (2016) for global analysis; Beyene et al (2018) and Schuenemann et al (2018) for developing countries; Lennox & Diukanova (2011) and Llop & Ponce-Alifonso (2016) for regional analysis and Dinar (2014) for a recent survey. 8 Nile contributes 83% of water followed by groundwater (11%) and non-conventional sources; i.e., recycling drainage water, treating sewage water and desalinating seawater.…”
Section: Contextmentioning
confidence: 99%